Evaluation and Implementation of Nutrition Surveillance System in Bukittinggi - Sulastri, Sulastri; Gusti, Aria; Eka P, Ade Suzana (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Nutritional surveillance monitors nutritional status to inform policy and programme decisions to improve community nutrition, including stunting. Chronic malnutrition and recurring illnesses cause stunting, which is when a child's length or height falls below the health minister's guidelines. Challenges include: not all Posyandu are active/covered low, not all targets have been input into the EPPGBM application (Toddlers and Pregnant Women), the use of the EPPGBM application in Community Health Centres has not been optimal, not all health workers and cadres have received height measurement training, coordination at each level, the monitoring system, and supervision to ensure height measurement quality. Due to its impact on the newborn, the first 1,000 days are critical. Permanent and lasting damage. Providing nutrition assistance at community health centre with surveillance can avoid stunting.Methods: The employed approach is participatory in nature, wherein partners are engaged to actively participate in various activities, while being supported by a dedicated staff that serves as a valuable resource and facilitator. The data analysis conducted for training purposes is to facilitate the implementation of the stunting surveillance programme, which is anticipated to encompass many sectors. This programme will primarily focus on monitoring and reporting nutrition-related activities, with a particular emphasis on stunting routines.